The effect of alkalization and esterification treatment on mechanical properties of water hyacinth fiber reinforced epoxy-resin composite - Sulardjaka, Sulardjaka; Iskandar, Norman; Manik, Parlindungan; Nurseto, Dwi Satrio (Eastern-European Journal of Enterprise Technologies, 2023)
This research investigates the effect of fiber pre-treatment on the mechanical and physical properties of unidirectional water hyacinth (WH) fiber reinforced epoxy resin composites. The water hyacinth fibers have been produced by mechanical processing. The 50–70 cm length of WH stems are brushed with an iron brush to mechanically extract the strands. The dry fibers then were pre-treated by alkalization and esterification. The alkalization ha ve been conducted by immersing the WH fibers on 2 %, 5 % and 10 % NaOH solution for 24 h. The esterification of WH fibers have been done using acetate anhydride. The composite with 15 %, 25 % and 35 % of unidirectional WH fibers was made by hand lay-up. After hand lay up process the WH composites then compacting with pressure compaction 5 MPa. Tensile test and was done based on ASTM D3039. The density of composites was tested based on Archimedes rule. Surface contaminants have been eliminated by fiber treatment. The NaOH treatment eliminated the surface’s wax and cuticle. The surface of fibers treated with 10 % NaOH was cleaner than those treated with 5 % NaOH. Fiber treatment has the effect of reducing fiber thickness.The tensile test results of the composite reinforced with WH fiber with NaOH treated and acetate anhydride show that the tensile strength of untreated WH fiber reinforced epoxy resin composites increased with the increase of % WH fiber. The tensile strength results that acetate anhydride treatment of WH fiber reinforced epoxy resin composites showed increased WH fiber increase the tensile strength of composite. The highest tensile strength of epoxy resin reinforced with WH fiber with acetate anhydride treatment